Dynamics of budget absorption: The role of budget political moderation on human resource regulation and competence in local governments - Lastri, Surna; Syamsidar, Syamsidar; Nasution, Emmi Suryani; Lokman, Farha Zafira Agos (Journal of Accounting and Investment, 2026)
Research aims: This study examines the effects of regulations, human resource competence, and budget politics on budget absorption. In addition, it seeks to analyze the moderating role of budget politics in strengthening or weakening the relationships between regulations, human resource competence, and budget absorption. Design/Methodology/Approach: This research adopted a quantitative approach using a questionnaire survey. The study population comprised all government officials from 27 regional apparatus work units in Nagan Raya Regency, Aceh Province, totaling 108 respondents, including service secretaries, financial administration officials, expenditure treasurers, and heads of finance subdivisions. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Research findings: The results indicate that budget politics positively influence public budget absorption, whereas regulation and human resource competence do not have a direct effect. The moderation analysis further reveals that budget politics has a significant negative moderating effect on the relationship between regulation and budget absorption, implying that heightened political intensity may weaken the effectiveness of regulatory frameworks. Conversely, budget politics does not moderate the relationship between human resource competence and public budget absorption.Theoretical contribution/Originality: This study has expanded the literature on the political budget cycle by emphasizing the significance of balancing political stability, regulatory flexibility, and adaptive human resource capacity to improve the effectiveness of public budget absorption.Practical/Policy implication: Local governments should design regulations that are adaptive to political dynamics, strengthen managerial human resource capacity, and optimize digital technologies to enhance transparency and efficiency in budget management.